Edukasi Kewirausahaan Dan Pelatihan Produk Kreatif Bagi Santri Kelas Vii Di Pondok Pesantren Modern Al-Rifa’ie 2 Malang - Erin Hartutik; Refi Ema Nur Eriva; Nafila Nur Haliza; Imroatul Chusnia; Ariffudin Ariffudin (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2026)
This community service program aimed to foster entrepreneurial spirit and provide basic creative skills to seventh-grade students at Pondok Pesantren Modern Al-Rifa’ie 2 The program adopted a participatory approach through experiential learning methods. The results showed that students developed a basic understanding of entrepreneurship, successfully produced simple creative products, and showed high enthusiasm throughout the process. The findings demonstrate that entrepreneurship education through practical training can be effectively implemented in Islamic boarding school environments when adapted to local context and student characteristic.